2015
DOI: 10.1177/1474904115589039
|View full text |Cite
|
Sign up to set email alerts
|

New empirical evidence on the effect of educational tracking on social inequalities in reading achievement

Abstract: One of the major imperatives behind the comprehensivisation of secondary education was the belief that postponing the age at which students are tracked in different educational routes would mitigate the effect of social background on educational outcomes. Comparative investigations of large-scale international student achievement tests in secondary education, such as PISA, have indeed suggested that individual test results depend less on social origin in countries that have postponed tracking age. However, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…The empirical evidence largely confirms that early tracking strengthens the influence of parental background on students' educational achievement, as tracking has a detrimental effect on low-achievers (Hanushek and Woessmann 2006;Schütz, Ursprung, and Woessmann 2008;Bol and van de Werfhorst 2013;Lavrijsen and Nicaise 2015). At the same time, in tracking regimes boys tend to be more often placed in lower tracks than girls (Van Hek, Buchmann, and Kraaykamp 2019).…”
Section: Theoretical Background and Related Literaturementioning
confidence: 60%
See 1 more Smart Citation
“…The empirical evidence largely confirms that early tracking strengthens the influence of parental background on students' educational achievement, as tracking has a detrimental effect on low-achievers (Hanushek and Woessmann 2006;Schütz, Ursprung, and Woessmann 2008;Bol and van de Werfhorst 2013;Lavrijsen and Nicaise 2015). At the same time, in tracking regimes boys tend to be more often placed in lower tracks than girls (Van Hek, Buchmann, and Kraaykamp 2019).…”
Section: Theoretical Background and Related Literaturementioning
confidence: 60%
“…To test the direct effects of early tracking a difference-in-differences approach was employed (see Ammermüller 2005;Waldinger 2007;Lavrijsen and Nicaise 2015). Combining PISA data with PIRLS or TIMSS datasets measuring achievement in the fourth grade provides an ideal setting, as PISA measures students after tracking has taken place in early tracking countries, while in late tracking countries there is no tracking at the age of 15.…”
Section: Early Trackingmentioning
confidence: 99%
“…Sawiński focused only on one dimension of differentiation: earlier or later tracking. As expected from the results of comparative studies, postponing the age of tracking is related to a weaker association between family socio-economic status (SES) and student achievement (see Betts 2011;Horn, 2009;Lavrijsen and Nicaise, 2015;Van de Werfhorst and Mijs, 2010). However, the age at tracking constitutes only one element of organising the educational system.…”
Section: Two Research Traditions On Educational Inequalitiesmentioning
confidence: 95%
“…Usually, tracks are hierarchically organized, which leads to a distinction between higher and lower tracks, and are based on the average academic performance of students. Most studies comparing education systems have shown that education systems with early tracking increase inequality in academic performance between students compared to education systems with late tracking (Ammermüller, ; Bauer & Riphahn, ; Brunello & Checchi, ; Hanushek & Wößmann, ; Horn, ; Lavrijsen & Nicaise, ; Marks, ; Schütz et al ., ; Wößmann, ). However, not all studies had this result (Waldinger, ).…”
Section: Introductionmentioning
confidence: 99%